2014, Nr. 15A, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Challenges of auditing and internal control Indrė Pečiulytė, Juozas Ruževičius, Quality audit typology and methodology, 8 Darius Vaicekauskas, Analysis and evaluation of Lithuanian public interest companies audit market, 26 Rasa Kanapickienė, Živilė Grundienė, Actions to detect fraud in financial statements, 37 Aleksandra Pečiūrienė, Analytical procedures in volatile business entities audit context, 47 Lukas Giriūnas, Jonas Mackevičius, The expression of the elements of the internal control system graphical representation, 62 Gintarė Giriūnienė, The research of professional ethics of tax auditor seeking the trust in tax, 73 Živilė Simonaitytė, Analysis of internal control models, 82 Problems of economics and finance Milda Švedienė, Astrida Slavickienė, The impact of notional defined contribution system (NDC) from the point of view of individual, 96 Artūras Jurgelevičius, Social economic risk analysis of Lithuania in the context of European Union countries, 106 Deimena Kiyak, Laura Paulionienė, Activity evaluation of Lithuania credit unions, 118 Jūratė Každailienė, Dalia Daujotaitė, Assessment of trade credit risk in business companies, 133 Emilija Narbuntaitė, Agnė Ramanauskaitė, The assessment of shadow economy in Lithuania, 149 Jovita Kalantaitė, Rasa Subačienė, Impact of Lithuanian tax reform to companies results, 162 Jonas Martinavičius, Preparation of trade specialists at VU faculty of economics and their correspondence to market needs, 178 Lukas Giriūnas, Jonas Mackevičius, Analysis of Professor Vladas Jurgutis thoughts on the money and its development in the Lithuanian scientific literature, 191